Engineering geology for tomorrow's cities - Culshaw, M. G. (Geological Society, 2009)
Summing up knowledge and understanding of engineering geology as is applies to the urban environment at the start of the 21st century, this volume demonstrates that: working standards are becoming internationalised; risk assessment is driving decision-making; geo-environmental change is becoming better understood; greater use of underground space is being made; and IT advances are improving subsurface visualization.
Consists of papers from the 10th International IAEG Congress in Nottingham in September 2006.
Keywords: Engineering geology -- Congresses.; elektronické knihy; electronic books